NGO’s Financial Reporting and Human Capital Development - Ahmed, Alim Al Ayub; Asadullah, A. B. M.; Rahman, Md. Mostafijur (American Journal of Trade and Policy, 2016)
The purpose of the study was to find out whether human capital development influences the quality of financial reporting of NGOs. The specific objectives of the study were to determine the relationship between human capital development and the quality of financial reporting, examine the relationship between human resource practices and the quality of financial reporting, examine the relationship between human capital development and human resource policy and examine if human resource practices moderate/ mediate the relationship between human capital development and the quality of financial reporting. The study adopted a cross-sectional parallel survey design with quantitative techniques and employed self-administered questionnaires to 60 respondents. The research data was coded and analyzed using the Statistical Package for Social Sciences (SPSS) version 20 to establish the statistical inferences. The Pearson correlation test reported that human capital development has a positive significant relationship with the quality of financial reporting (r = .551, p< .01; two tailed). The study concluded that education, skills, knowledge, experience, interest and values were significantly positively related with financial reporting quality (r = .503, p < .01; r = .407, p < .01; r = .518, p < .01; r = .213, p < .10 and r = .476, p < .01 respectively). Furthermore, personality positively relates to financial reporting quality (r = .165, p>0.10). Some recommendations were then formulated thus: Organizations should encourage and support their accounting staff to attain professional qualifications. The staff should strive to attain membership of professional accounting bodies. The staff should also be motivated as well as regularly trained on job. Management should observe strict adherence to accounting and financial manuals. Organizations should also reinforce workplace policies as well as review their current accounting systems to identify gaps and then put in place steps to fill those gaps.